Analisis Distribusi Kekayaan Dalam Prespektif Ekonomi Islam Menurut Ibn Kaldun - M, Mawardi; Mahera, Rofiqo Meili (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
According to Ibn Khaldun, a great thinker in the social and economic fields. The type of research used is qualitative research with a descriptive analytical approach. In this study, the author examines the main concepts in Ibn Khaldun's thoughts related to the distribution of wealth, such as the theory of